Adaptive Decision-making for Robotic tasks - Tsymbal, O.; Bronnikov, A.; Yerokhin, A. (My University, 2019)
There is proposed the analysis of decisionmaking problem in its application for flexible integrated robotic systems. The intelligent systems in form of problemsolving components are considered as key component of automated control systems. There is observed the proposed concept of adaptive decision-maling for flexible robotic systems, based on a set of models and methods of adaptive decision-making, data science methods.
Keywords: adaptivity; decision-making; mobile robot; flexible integrated system; data science